Analyzing the gender representation status of Ethiopian primary school textbooks and teachers’ insight - Mollaw Abraha (Cogent Education)
The present study aims to investigate the status of gender representation in the recently published grade six English textbook of Ethiopia. To accomplish this, a content analysis research design was utilized. The researcher sourced data from the grade six English language textbook and English language teachers by employing random and purposive sampling techniques respectively. Data were collected from both the textbook and teachers through content analysis and interviews, correspondingly, and were subsequently analyzed using both quantitative and qualitative methods. The findings indicated that the Ethiopian grade six English language textbook exhibited gender bias, favoring male representations over female ones in terms of occupational roles, topic dominance, and language usage involving proper nouns, pronouns, and common nouns. Moreover, the textbook linked its characters to masculinity, emphasizing male ideas over female in various sections/analysis units, which reinforced male superiority and ridiculed female peers in social context. As a result, gender inequities were evident throughout the textbook’s content. Consequently, it is essential for stakeholders – especially textbook developers – to ensure that their considerations of textbooks’ gender treatment promote inclusivity and gender neutrality.